Demographic and Clinical Features Associated with in-Hospital Mortality in Egyptian COVID-19 Patients: A Retrospective Cohort Study - Asem, Noha; Hassany, Mohamed; Taema, Khaled; Masoud, Hossam; Elassal, Gehan; Kamal, Ehab; Amin, Wagdy Abdel Moneim; AbdelBary, Akram; Abdel-Baki, Amin Mohamed; Zaky, Samy; Abdalmohsen, Ahmad Said; Ibrahim, Hamdy Mohamed; et al. (Open Access Macedonian Journal of Medical Sciences, 2021)
Aim: We evaluated in this study the demographic and clinical characteristics of COVID-19 disease in Egyptian population with special consideration for its mortality predictors. Methods: 8162 participants (mean age 48.7±17.3 years,54.5% males) with RT-PCR positive COVID-19 were included. The electronic medical records were reviewed for demographic, clinical, laboratory, and radiologic features. The primary outcome was the in-hospital mortality rate. Results: The in-hospital mortality was 11.2%. There was a statistically significant strong association of in-hospital mortality with age >60 years old (OR:4.7; 95% CI 4.1-5.4;p<0.001), diabetes mellitus (OR:4.6; 95% CI 3.99-5.32;p<0.001), hypertension (OR:3.9; 95% CI 3.4-4.5;p<0.001), coronary artery disease (OR:2.7; 95% CI 2.2-3.2;p<0.001), chronic obstructive pulmonary disease (OR:2.1; 95% CI 1.7-2.5;p<0.001), chronic kidney disease (OR:4.8; 95% CI 3.9-5.9;p<0.001), malignancy (OR:3.7; 95% CI 2.3-5.75;p<0.001), neutrophil-lymphocyte ratio >3.1 (OR:6.4; 95% CI 4.4-9.5;P< 0.001), and ground glass opacities (GGOs) in CT chest (OR:3.5; 95% CI 2.84-4.4;P<0.001), respectively. There was a statistically significant moderate association of in-hospital mortality with male gender (OR:1.6; 95% CI 1.38-1.83;p<0.001) and smoking (OR:1.6; 95% CI 1.3-1.9;p<0.001). GGOs was reported as the most common CT finding (occurred in 73.1% of the study participants). Conclusion: This multicenter, retrospective study ascertained the higher in-hospital mortality rate in Egyptian COVID-19 patients with different comorbidities.